b - Abascal, Julio; Barbosa, Simone; Fetter, Mirko; Gross, Tom.; Palanque, Philippe; Winckler, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
The four-volume set LNCS 9296-9299 constitutes the refereed proceedings of the 15th IFIP TC13 International Conference on Human-Computer Interaction, INTERACT 2015, held in Bamberg, Germany, in September 2015. The 47 papers included in the second volume are organized in topical sections on computer-supported cooperative work and social computing; end-user development; evaluation methods / usability evaluation; eye tracking; gesture interaction; HCI and security; HCI for developing regions and social development; HCI for education.
Computer-supported cooperative work and social computing -- End-user development -- Evaluation methods/usability evaluation -- Eye tracking -- Gesture interaction -- HCI and security -- HCI for developing regions and social development -- HCI for education.
Keywords: Computer science; Artificial intelligence; Education; Software engineering; User Interfaces and Human Computer Interaction; Information Systems Applications (incl. Internet).; Artificial Intelligence; Computers and Education; Software Engineering